PGF2 supplementation as a strategy to improve post-thawing motility of spermatozoa in Waringin sheep - Husnurrizal, Husnurrizal; Azim, Muhammad; Thasmi, Cut Nila; Hafizuddin, Hafizuddin (The Faculty of Veterinary Medicine of Syiah Kuala University, 2025)
Background and Aim: This study aimed to evaluate the effect of prostaglandin F2 (PGF2) supplementation in semen extenders on the post-thaw sperm motility of Waringin rams.Materials and Methods: Semen was collected from Waringin rams, diluted with Andromed extender, and divided into three treatment groups: control (K0) without PGF2, P1 with 37.5 g PGF2, and P2 with 75 g PGF2.Results : The results showed that post-thaw sperm motility in P1 (49.33%) and P2 (54.00%) was significantly higher than in the control group K0 (25.33%) (P 0.05), although no significant difference was observed between P1 and P2 (P 0.05). Additionally, pre-freezing sperm motility also increased in P1 (75.00%) and P2 (82.33%) compared to K0 (43.67%).Conclusion: It is concluded that PGF2 supplementation in semen extenders can improve the post-thaw motility of Waringin ram spermatozoa, with a 75 g dosage yielding the most optimal effect.